Anti-corrosion characteristics of ampicillin and flucloxacillin drugs: A theoretical study - Gece, Gökhan; Bilgiç, Semra (Ankara Üniversitesi, 2023)
To determine the inhibition efficiency of a corrosion inhibitor, multiple experimental measurements need to be carried out, which is a time-consuming and resource-intensive task. On the other hand, quantum chemical methods are useful research tools for corrosion scientists. In this study, the corrosion inhibition effects of ampicillin and flucloxacillin at the molecular level were evaluated considering some descriptors by density functional theory (DFT) at B3LYP/6-311++G(d,p) level.
Keywords: Computational Chemistry; Hesaplamalı Kimya